2004
DOI: 10.1254/jphs.fp0040314
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Selective Inhibitor of Secretory Phospholipase A2, S-5920/LY315920Na, on Experimental Acute Pancreatitis in Rats

Abstract: Abstract. We investigated the efficacy of a potent inhibitor of secretory phospholipase A 2 (sPLA 2 ), S-5920 / LY315920Na, in an experimental model of acute pancreatitis in rats. Combined intraductal injection of sodium taurocholate (5 mg / rat) and porcine pancreatic sPLA 2 -IB (300 m g / rat) caused severe hemorrhagic necrotizing pancreatitis resulting in high mortality, along with rapid increases of catalytic PLA 2 and lipase activities in plasma and ascites and with gradual increases of plasma amylase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 31 publications
(36 reference statements)
0
10
0
1
Order By: Relevance
“…153 LY315920Na showed prophylactic effects on the high mortality, severe pancreas tissue damage, and blood biochemical changes in a lipolytic enzyme-related severe pancreatitis model. 154 Varespladib was advanced in clinical trials as an intravenously-administered therapy for sepsis-induced systemic inflammatory response syndrome. 155 At the end of the Phase I study, Varespladib was found to have an acceptable safety profile in patients with severe sepsis.…”
Section: Secreted Phospholipase A2 (Spla2 Groups I Ii Iii V Ixmentioning
confidence: 99%
“…153 LY315920Na showed prophylactic effects on the high mortality, severe pancreas tissue damage, and blood biochemical changes in a lipolytic enzyme-related severe pancreatitis model. 154 Varespladib was advanced in clinical trials as an intravenously-administered therapy for sepsis-induced systemic inflammatory response syndrome. 155 At the end of the Phase I study, Varespladib was found to have an acceptable safety profile in patients with severe sepsis.…”
Section: Secreted Phospholipase A2 (Spla2 Groups I Ii Iii V Ixmentioning
confidence: 99%
“…51 These drugs are effective anti-inflammatory agents in experimental models of inflammatory diseases 52 and have been used in clinical trials in patients with rheumatoid arthritis 53 and bronchial asthma. 54 However, both of these trials failed to demonstrate a significant therapeutic effect.…”
Section: Therapeutic Implications Of Spla 2 Inhibitors In Inflammatormentioning
confidence: 99%
“…Both models therefore support a specific sPLA 2 group IIA inhibitory role for LY315920 (9) in vivo although the 10 fold difference in effectiveness that was observed could indicate non-specific binding to other BAL cell proteins. The pharmacodynamics of LY315920 (9) were evaluated in transgenic mice that expressed human sPLA 2 protein in their LY315920 (9) has been evaluated in a rat model of acute pancreatitis [84], a condition in which elevated levels of sPLA 2 group IIA and group IB are known to be associated [85,86]. Pancreatitis was induced by infusion of a bile acid (sodium taurocholate) together with bovine pancreatic sPLA 2 group IB into the common biliopancreatic duct resulting in severe haemorrhagic pancreatitis.…”
Section: Inhibitorsmentioning
confidence: 99%